Introductory econometrics a modern approach - Wooldridge, Jeffrey M. 1960- (Australia South Western, Cengage Learning, 2009)
"Econometrics is based upon development of statistical methods for estimating economic relationships, testing economic theories, and evaluating and implementing government and business policy. The most common application of econometrics is the forecasting of such important macroeconomic variables as interest rates, inflation rates, and gross domestic product."
Regression analysis with cross-sectional data -- Regression analysis with time series data -- Advanced topics.
Access code card to eResources: Data sets, Solutions manual, and EconApps included.
Keywords: Econometrics